Let's go out for a drink after work! The relation between leisure time spent with colleagues and employees' life satisfaction. (2nd January 2018) - Endrejat, Paul C.; Barthauer, Luisa; Kauffeld, Simone
ABSTRACT: Despite the tremendous research studying the factors that influence employees' well-being, the effect of what happens when leisure time is spent with colleagues remains yet unexamined. Building on the conservation of resources theory, we propose that leisure time spent with colleagues could be understood as a resource, especially for those individuals who have few friends at their workplace. In a cross-sectional design, 136 university employees provided information about the number of friends they have at work, the amount of leisure time spent with befriended colleagues, and their life satisfaction. Results suggest that a larger network of friends at work is positively associated with life satisfaction. Furthermore, the effect of the number of friends at work on life satisfaction is moderated by the amount of leisure time spent with befriended colleagues. Employees who have few friends at work report more life satisfaction, if they spend more leisure time with befriended colleagues, whereas such an effect was not found for employees with a large friend network at work. These results are placed into the context of current discussions about work-life-blending.